Satyagraha prisoners on Natal’s coal mines (Historia, 2021)
In 1913 under the leadership of Gandhi, the first "mass" political resistance was launched in South Africa. The key sites of resistance were in Natal and the Transvaal. This resistance was popularly known as the Satyagraha campaign or the Indian Strike. Well over 20 000 men, women and children engaged in protest action against discriminatory legislation that restricted their economic, social and political mobility. The historiography of the 1913 Satyagraha Campaign is substantial, but there are gaps of coverage on the incarceration and treatment of prisoners. The coal mines in the Natal Midlands became another site of resistance in the aftermath of the campaign. This article documents prisoner/captor relations in the aftermath of the campaign on the coal mines. Indian prisoners were subjected to flogging, poor rations and at times, ringleaders were assaulted severely. These lesser known narratives add to the current historiography by highlighting mine authorities' attitudes and policy towards prisoners in the context of control, repression and coercion as well as the nature of the prisoner and captor relationship in the Satyagraha campaign of 1913.
Keywords: Indians; satyagraha; coal mining; resistance; Natal